Ephus: Multipurpose Data Acquisition Software for Neuroscience Experiments - Suter, Benjamin A.; O'Connor, Timothy; Iyer, Vijay; Petreanu, Leopoldo; Hooks, Bryan M.; Kiritani, Taro; Svoboda, K.; Shepherd, Gordon M. (Frontiers in Neural Circuits, 2010)
Physiological measurements in neuroscience experiments often involve complex stimulus paradigms and multiple data channels. Ephus (http://www.ephus.org) is an open-source software package designed for general-purpose data acquisition and instrument control. Ephus operates as a collection of modular programs, including an ephys program for standard whole-cell recording with single or multiple electrodes in typical electrophysiological experiments, and a mapper program for synaptic circuit mapping experiments involving laser scanning photostimulation based on glutamate uncaging or channelrhodopsin-2 excitation. Custom user functions allow user-extensibility at multiple levels, including on-line analysis and closed-loop experiments, where experimental parameters can be changed based on recently acquired data, such as during in vivo behavioral experiments. Ephus is compatible with a variety of data acquisition and imaging hardware. This paper describes the main features and modules of Ephus and their use in representative experimental applications.